Promising Medicinal Plants with Diuretic Potential Used in Brazil: State of the Art, Challenges, and Prospects - de Souza, Priscila; Mariano, Luísa Nathália Bolda; Cechinel-Zanchett, Camile Cecconi; Cechinel-Filho, Valdir (Planta Medica, 2020)
Medicinal plants are used in traditional medicine to treat a wide range of ailments. The knowledge of them is handed down from generation to generation and is described in several pharmacopoeia and in the general literature. The immense biodiversity of the Brazilian flora, covering about 25% of all plant species worldwide, makes Brazil a huge potential source of medicinal plants. Indeed, many of these plant species are already used in the Brazilian ethnopharmacology for their probable effect to induce diuresis, to reduce fluid retention, and to treat cardiovascular and renal disorders. This review article describes and discusses the main native Brazilian medicinal plants (including some of their isolated compounds) used as diuretics. It also gives a comprehensive analysis of the most relevant scientific studies presented to date, as well as addressing a special topic with future prospects for plant species that have not yet been scientifically studied. In brief, several plants can be indicated for more detailed study, with a view to obtain scientific subsidies for a new and effective diuretic medicine in the future. These include Bauhinia forficata, Leandra dasytricha, and Tropaeolum majus. Other species have reputed medicinal properties but lack experimental assays to demonstrate their pharmacological effects (e.g., Mikania hirsutissima, Phyllanthus niruri, and Tagetes minuta). Several active principles are indicated as responsible for the diuretic effects of the plants studied, with emphasis on phenolic compounds as flavonoids, phenolic acids, and xanthones. These results should encourage more detailed preclinical, clinical, and phytochemical investigations on Brazilian plants in the future.
Keywords: diuresis; Brazilian biodiversity; folk medicine; preclinical studies